Vascular Anomalies in Pancreaticoduodenectomy: A Lesson Learned - Joana E. Ochoa; David T. Pointer; John B. Hamner (Case Reports in Surgery)
It is essential to identify any variant anatomy prior to surgery as this could have a drastic effect on surgical planning. We describe a case in which two vascular irregularities, an Arc of Buhler and celiac stenosis, were identified on angiogram after completion of a pancreaticoduodenectomy. While there could have been catastrophic results from his surgery in the setting of celiac stenosis, the presence of the aberrant Arc of Buhler allowed this patient to emerge without any permanent morbidity.